SCIENTIFIC FOUNDATIONS OF INTEGRATED DEVELOPMENT OF PHYSICAL AND PSYCHOLOGICAL PREPARATION OF ATHLETES IN FOOTBALL TRAINING - Xamroyev Behruz Xalimovich (International Journal of Literature and Language Studies, 2026)
This article is devoted to the study of the scientific foundations of the comprehensive development of physical and psychological preparation of athletes during football training. In modern sports practice, not only the physical qualities of football players, but also their psychological stability, ability to make quick decisions and stress resistance are of great importance. The article covers the issues of effective organization of football training, correct distribution of loads, development of technical and tactical skills, as well as strengthening the motivation and psychological state of athletes. The importance of using modern pedagogical and psychological approaches in the training process is also analyzed.